Multiformat Accessible Menus: A tool for social inclusion and autonomy for all - Gil, Henrique Teixeira (2024)
Several studies have shown that accessibility to information is not yet considered a full and guaranteed right for people with Specific Needs. To respond to this need, restaurant menus were adapted using inclusive design, accessible communication, and multiformat (braille, pictographic symbols for communication, QR code with audio and photographs). To validate this resource as a tool for promoting social inclusion and autonomy for people with Specific Needs, this research was based on a multiple case study involving two restaurants in a non-formal education context. The data collection techniques and instruments used were semi-structured interviews (n=1), field notes, focus groupswith restaurant owners and employees (n=4), and questionnaire for restaurant customers (n=80). Using content analysis and a descriptive statistical analysis, we found that all the categories of analysis revealed significant and interesting values regarding the perceptions of the people involved in the study. The results obtained in this exploratory survey showed that 97% of respondents believe that tourism services should provide accessible menus to ensure accessibility and participation for all. The data also shows that adapting menus in accessible communication can be a tool to promote inclusion (98%) and autonomy (95%) for people with Specific Needs. Despite being an instrument that needs further scientific research, implementing accessible menus in restaurants could enable full and effective participation for all people, regardless of their Specific Needs, granting them the autonomy and independence that give them dignity.